Unusual combinatorial involvement of poly-A/T tracts in organizing genes and chromatin in Dictyostelium - Chang, Gue Su; Noegel, Angelika A.; Mavrich, Travis N.; Müller, Rolf; Tomsho, Lynn; Ward, Elissa; Felder, Marius; Jiang, Cizhong; Eichinger, Ludwig; Glöckner, Gernot; Schuster, Stephan C.; Pugh, B. Franklin (Genome Research, 2012)
Dictyostelium discoideum is an amoebozoa that exists in both a free-living unicellular and a multicellular form. It is situated in a deep branch in the evolutionary tree and is particularly noteworthy in having a very A/T-rich genome. Dictyostelium provides an ideal system to examine the extreme to which nucleotide bias may be employed in organizing promoters, genes, and nucleosomes across a genome. We find that Dictyostelium genes are demarcated precisely at their 5′ ends by poly-T tracts and precisely at their 3′ ends by poly-A tracts. These tracts are also associated with nucleosome-free regions and are embedded with precisely positioned TATA boxes. Homo- and heteropolymeric tracts of A and T demarcate nucleosome border regions. Together, these findings reveal the presence of a variety of functionally distinct polymeric A/T elements. Strikingly, Dictyostelium chromatin may be organized in di-nucleosome units but is otherwise organized as in animals. This includes a +1 nucleosome in a position that predicts the presence of a paused RNA polymerase II. Indeed, we find a strong phylogenetic relationship between the presence of the NELF pausing factor and positioning of the +1 nucleosome. Pausing and +1 nucleosome positioning may have coevolved in animals.
10.1101/gr.131649.111